If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 1(22) = 0 Multiply 1 * 22 2y + 22 = 0 Reorder the terms: 22 + 2y = 0 Solving 22 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 2y = 0 + -22 Combine like terms: 22 + -22 = 0 0 + 2y = 0 + -22 2y = 0 + -22 Combine like terms: 0 + -22 = -22 2y = -22 Divide each side by '2'. y = -11 Simplifying y = -11
| a=6+-2b | | 21=6x-33 | | 88-2b=-16b-22 | | 15x^7y^6= | | 7(t-2)-t=6 | | 7(y-3)=6(y-4) | | 31+9x=175 | | 11x-147-2x=96 | | -5(t-4)= | | -7-3*2-1= | | -10=12y/5+3(-9y/5-2) | | 2(x+3)+15= | | -2x-75-9=145 | | -7x-2x-61=92 | | -27-x+4x=9 | | x-10+y-22(x+y)+y= | | 7x+2-5x-7= | | -72+3x+6x=117 | | 4+4+1+3n= | | 9x+21=111 | | y=32-14x-5 | | 3x+9-6x=33+3x | | 7(8x-15)=175 | | 5x^2+24x-15=0 | | 2x+16=44 | | 5x^2=25x-15 | | -.75+.125=x | | 6(9x-14)=402 | | 11x+x^2+30=0 | | 6(8x+7)=426 | | 5x-3x-35=11 | | -2(x-5)+2=12 |